2021
DOI: 10.4028/www.scientific.net/kem.884.117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Molar Ratio of Acetic Acid to UFA and Stirring Velocity in the Tung Oil Epoxidation

Abstract: Epoxidation of the unsaturated fatty acids (UFA) in Tung oil provides a very interesting opportunity in the research and development of advanced materials. Tung oil is one of non-edible vegetable oils and epoxidized Tung oil (ETO) also provides benefits in terms of renewable and eco-friendly. This research evaluated the influences of acetic acid's molar ratio to UFA and stirring velocity in the epoxidation process of Tung oil. Epoxidation was carried out in a batch reactor using peroxyacetic acid produced in-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…These observations suggested that the formation of hydroxyl groups (-OH) is contingent upon the presence of an oxirane ring, and their concentration increases when there is an abundance of oxirane rings and heightened molecular kinetics in the reaction medium. This statement aligns with findings from previous research [2,3,19].…”
Section: Effect Of Temperature On the Iodine Value And Oxirane Numbersupporting
confidence: 91%
See 2 more Smart Citations
“…These observations suggested that the formation of hydroxyl groups (-OH) is contingent upon the presence of an oxirane ring, and their concentration increases when there is an abundance of oxirane rings and heightened molecular kinetics in the reaction medium. This statement aligns with findings from previous research [2,3,19].…”
Section: Effect Of Temperature On the Iodine Value And Oxirane Numbersupporting
confidence: 91%
“…The samples are cooled and separated to obtain epoxidized tamanu oil, whose iodine and oxirane values will be analysed. The analysis was carried out using methods from previous research [1,3,18].…”
Section: Epoxidation Processmentioning
confidence: 99%
See 1 more Smart Citation